Towards a circular project, between architecture and exhibition design. Digital platforms for reuse practices - Davide Crippa; Massimiliano Cason Villa; Barbara Di Prete; Lucia Ratti; Agnese Rebaglio; Marco Zanini; Francesca Zanotto (Agathón)
Sustainable development and digital transition find wide space in the debate around design disciplines that take up the theme at different paces. While architectural and urban design research has long been working towards innovating design and construction paradigms in a sustainable and circular sense, exhibition design has slowly integrated these aspects into its creation and management structures. From this perspective, the digital transition represents an excellent opportunity to develop integrated systems for circular production chains. The text explores the state of arts in architecture and exhibition design, identifying innovation trajectories within cases of emblematic collaborative platforms, and highlighting their limitations and mutual lessons learned.